The Philippine economy in the 1970's : prospects and problems of development - Quezon, Philippines (Quezon City : Institute of Economic Development and Research, University of the Philippines; The Private Development Corporation of the Philippines, 1972)
In the current lecture series a closer look is taken at a number of important industries: manufacturing, wood, power, mining, rice and sugar.
Papers and discussions from a public lecture series sponsored by the Institute of Economic Development and Research, held at Makati, Rizal, Nov. 25 1969-Jan. 9, 1970.
Includes bibliographical references.
rpm 15/06/2017
Loans
Keywords: Philippines--Economic conditions; Philippines--Economic policy; Philippines